Accelerated ice mass depletion revealed by low‐degree gravity field from satellite laser ranging: Greenland, 1991–2011. Issue 17 (11th September 2013) - Matsuo, Koji; Chao, Benjamin F.; Otsubo, Toshimichi; Heki, Kosuke
Abstract [1] We detect the acceleration of ice mass depletion in Greenland for the period 1991–2011 from the low‐degree gravity field up to degree and order 4 derived from the Satellite Laser Ranging (SLR) data. Between 2003 and 2011, during the era when the GRACE (Gravity Recovery and Climate Experiment) satellite data are available, our SLR results of gravity changes agree well with GRACE showing significant negative patterns in Greenland. Prior to that, the SLR linear trend maps show a near balance in Greenland ice mass during 1991–2002 (after the glacial isostatic adjustment is accounted for using model values). We further confirm the consistency of our SLR results with the vertical crustal uplift of the region observed by the Global Positining System (GPS) which manifests ice mass loading/unloading. Thus, the SLR data series constitute a continuous benchmark for the time history of the Greenland ice mass changes for over two decades.